NSE/GCS in perioperative period on Seventh day as an independent predictor of 90-day outcome in patients with severe traumatic brain injury - Zhu, Chunying; Liu, Xiaona; Wang, Huan; Zhang, Yingfu; Li, Wei (Journal of Medical Biochemistry, 2025)
Summary: Background and Objectives: Traumatic brain injury (TBI) can lead to secondary damage that affects patient prognosis. Neuron-specific enolase (NSE) in the blood is a marker of nerve damage, while the Glasgow Coma Scale (GCS) score indicates patient consciousness. The ratio of NSE to GCS (NGR) during the perioperative period can assess the 90-day prognosis in severe TBI patients. Methods: This study involved 63 severe TBI patients. We collected their clinical and preadmission lab data. After admission, we provided personalized comprehensive treatment, including blood tests, interleukin 6 (IL-6), NSE, blood osmotic pressure (OSM), procalcitonin (PCT), and D-dimer (DD). We evaluated GCS score on Day 7 to calculate NGR. Using logistic regression and receiver operating characteristic (ROC) curve, we analyzed Pre-admission NLR0, and NSE7, GCS7, and NGR7 on the seventh day of admission. Results: Patients with poor 90-day outcomes were older, had longer hospital stays, and showed higher NLR0 and IL-6 levels on admission (all P < 0.05). NLR0, NSE7, GCS7 scores, and NGR7 independently predicted poor outcomes in severe TBI patients. NGR7 showed a strong Pearson r value (r = -0.702, p < 0.0001) and the highest diagnostic accuracy for 90-day prognosis [area under the curve (AUC) = 0.932; 95% CI = 0.872-0.993, with a cut-off value of 4.69, sensitivity of 86.49%, and specificity of 92.31%]. TBI patients with higher NGR on the seventh day after admission were more likely to experience unfavorable neurological outcomes.  Conclusion: NGR on the seventh day after admission significantly predicts the 90-day outcomes in severe TBI patients.
Keywords: Neuron-specific enolase, Glasgow Coma Scale, biomarker, Prognosis, Traumatic brain injury